Analysing sexual communication messages in Durex condom advertisement from marital standpoints - Alwi Putra Ramadhan; Novin Farid Styo Wibowo; Moch Fuad Nasvian; Mohd Hilmi Bakar (Jurnal Studi Komunikasi, 2024)
This research aims to explore the reception of sexual communication messages within the context of marital relationships in the Durex "Unequal Dinner" advertisement series. The method employed in this study is qualitative-descriptive, utilising Stuart Hall's Encoding-Decoding Theory to understand the reception by the subjects. Data was collected through in-depth interviews with four married female subjects born between 1981 and 1996 from the millennial generation. They reside in East Java, Indonesia, have been married for less than 10 years, and are parents. The research highlights differences in the reception of the subjects, stemming from their diverse experiences and backgrounds. Factors such as geographical distance, societal culture, and sexual education influence how they receive the sexual communication messages presented in the advertisement. Simultaneously, a dominant-hegemonic narrative position was observed in the subjects' receptions, indicating a close alignment between their experiences and the sexual communication messages conveyed by the Durex "Unequal Dinner" advertisement series. However, it does not guarantee the subjects' interest in purchasing Durex products.